Розв'яжіть: 2sin x cos x = 2cos ( - ) -√3 = 0

alikachara alikachara    2   23.08.2019 05:00    0

Ответы
Fosa1 Fosa1  05.10.2020 13:55
По формуле синуса двойного аргумента:
sin2x = \frac{ \sqrt{3} }{2}
2x = (-1)^{n}\frac{ \pi }{3} + \pi n, n ∈ Z
x = (-1)^{n}\frac{ \pi }{6} + \frac{\pi n}{2}, n ∈ Z

2cos( \frac{ \pi }{4}- \frac{x}{2} ) = \sqrt{3}
cos( -\frac{ \pi }{4}+ \frac{x}{2} ) = \frac{ \sqrt{3} }{2}
-\frac{ \pi }{4} + \frac{x}{2} = ±\frac{ \pi }{6} + 2 \pi n, n ∈ Z
x = ±\frac{ \pi }{3} + \frac{ \pi }{2} + 4 \pi n, n ∈ Z
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра